Metabolic and Molecular Changes of the Phenylpropanoid Pathway in Tomato (Solanum lycopersicum) Lines Carrying Different Solanum pennellii Wild Chromosomal Regions - Rigano, Maria Manuela; Raiola, Assunta; Docimo, Teresa; Ruggieri, Valentino; Calafiore, Roberta; Vitaglione, Paola; Ferracane, Rosalia; Frusciante, Luigi; Barone, Amalia (Frontiers in Plant Science, 2016)
Solanum lycopersicum represents an important dietary source of bioactive compounds including the antioxidants flavonoids and phenolic acids. We previously identified two genotypes (IL7-3 and IL12-4) carrying loci from the wild species Solanum pennellii, which increased antioxidants in the fruit. Successively, these lines were crossed and two genotypes carrying both introgressions at the homozygous condition (DHO88 and DHO88-SL) were selected. The amount of total antioxidant compounds was increased in DHOs compared to both ILs and the control genotype M82. In order to understand the genetic mechanisms underlying the positive interaction between the two wild regions pyramided in DHO genotypes, detailed analyses of the metabolites accumulated in the fruit were carried out by colorimetric methods and LC/MS/MS. These analyses evidenced a lower content of flavonoids in DHOs and in ILs, compared to M82. By contrast, in the DHOs the relative content of phenolic acids increased, particularly the fraction of hexoses, thus evidencing a redirection of the phenylpropanoid flux towards the biosynthesis of phenolic acid glycosides in these genotypes. In addition, the line DHO88 exhibited a lower content of free phenolic acids compared to M82. Interestingly, the two DHOs analyzed differ in the size of the wild region on chromosome 12. Genes mapping in the introgression regions were further investigated. Several genes of the phenylpropanoid biosynthetic pathway were identified, such as one 4-coumarate:CoA ligase and two UDP-glycosyltransferases in the region 12-4 and one chalcone isomerase and one UDP-glycosyltransferase in the region 7-3. Transcriptomic analyses demonstrated a different expression of the detected genes in the ILs and in the DHOs compared to M82.These analyses, combined with biochemical analyses, suggested a central role of the 4-coumarate:CoA ligase in redirecting the phenylpropanoid pathways towards the biosynthesis of phenolic acids in the pyramided lines. Moreover, analyses here carried out suggest the presence in the introgression regions of novel regulatory proteins, such as one Myb4 detected on chromosome 7 and one bHLH detected in chromosome 12. Overall our data indicates that structural and regulatory genes identified in this study might have a key role for the manipulation of the phenylpropanoid metabolic pathway in tomato fruit.